A novel approach for Direct Load Control of residential air conditioners for Demand Side Management in developing regions. (1st November 2022) - Rama Curiel, José Adrián; Thakur, Jagruti
Abstract: The rapid growth of air conditioners (ACs) in developing regions exacerbates some of the issues present in their electricity systems. Direct Load Control strategies can manage peak loads for optimizing energy usage for users and utilities. When applied to air conditioning, these strategies can be used for Demand Side Management which has not been fully explored for developing regions. In this paper a novel Direct Load Control mechanism is proposed, wherein control is based on technical constraints (generation capacity). To determine the effects of the proposed mechanism, a case study of the Indian State of Karnataka is carried out. The results indicate 0.88% energy savings and a reduction of almost 2% in regional peak loads in a state where only around 5% of all households have AC units. The case study shows that an AC Direct Load Control can have significant economic and environmental impacts, and can help improve current energy, water and climate issues. Continuous improvements in both energy access and economic conditions of developing regions are leading to a larger number of AC's installed, meaning that a mechanism that enables sustainable AC consumption could be of great use for all the stakeholders in the developing countries' electricity sectors. Highlights : A novel Direct Load Control for residential air conditioning is proposed. The control can be implemented in developing regions without price-based markets. A case study of the novel control shows a summer demand reduction of 0.88%. The reduction of the demand leads to environmental and economic benefits. The proposed control reduces negative impacts of growing air conditioning demand.